Comparison of Intravenous Anesthetic Agents for the Treatment of Refractory Status Epilepticus - Reznik, Michael E. (J Clin Med, 2016)
Status epilepticus that cannot be controlled with first- and second-line agents is called refractory status epilepticus (RSE), a condition that is associated with significant morbidity and mortality. Most experts agree that treatment of RSE necessitates the use of continuous infusion intravenous anesthetic drugs such as midazolam, propofol, pentobarbital, thiopental, and ketamine, each of which has its own unique characteristics. This review compares the various anesthetic agents while providing an approach to their use in adult patients, along with possible associated complications.